(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article presents the results of the treatment of surgical pathologies of the abdominal cavity in newborns in 2021-2024 in the department of neonatal surgery of the Bukhara Regional Multidisciplinary Children’s Medical Center. In recent years, there have been frequent postoperative complications and high mortality in intestinal obstruction in newborns, sometimes reaching up to 50%. A partial analysis of the causes of complications was performed, it was associated not only with late treatment of patients, severe complications, but also the lack of a unified program of preoperative management and reasonable surgical tactics in each specific clinical case.